Memaknai sesamaku manusia dengan kasih inkarnatif di era Sociaety 5.0 menurut Lukas 10:25-37 - Lau, Anika Regina; Samosir, Verawati Dosmaria; Koagouw, Deisy Yona (STT Arastamar Wamena, 2025)
The parable of the good Samaritan in Luke 10:25-37 emphasizes incarnate love that transcends ethnicity, religion, and social status. The 5.0 era has created a new civilization in human life, where the world is digitally connected but gives birth to a highly individualistic nature in human life. Therefore, understanding the meaning of